Vulvovaginal candidiasis and asymptomatic vaginal colonization in Portugal: Epidemiology, risk factors and antifungal pattern - Fernandes, Ângela (2022)
Vulvovaginal candidiasis (VVC) has been identified as a global issue of concern due to its clinical, social and economic implications. The emerging relevance of VVC makes it crucial to increase the knowledge on its epidemiological and etiological features in order to improve its prevention and treatment. Thus, this study aimed to reveal the incidence, microbiology, antifungal pattern and risk factors of VVC in Portugal. For that, high vaginal samples were collected from 470 symptomatic and asymptomatic participants; Candida spp. were identified with molecular techniques and their antifungal susceptibility was analyzed with E-tests. The results revealed an incidence of VVC among women with vulvovaginitis of 74.4\\%. Furthermore, 63.7\\% of asymptomatic women were colonized with Candida spp. Importantly, women with history of recurrent vaginal infections, those who use over-the-counter antifungals, oral contraceptive pills and non-cotton underwear were found to be at significantly higher risk of developing VVC. Candida albicans was the most common species (59\\%), followed by Candida glabrata (27\\%), in a total of eight distinct species, with similar distribution among colonized and infected participants. Of note, various isolates, especially of the most common species, showed low susceptibility towards fluconazole. In contrast, only few isolates showed low susceptibility towards caspofungin. Overall, this study suggests that the identification of species causing VVC and their antifungal susceptibility are urgently needed in clinical practice in order to improve the decision for the most adequate treatment. It also suggests that avoiding certain risk behaviors may prevent the development of VVC.Vaginal candidiasis (VVC) is a relevant infection worldwide. In this study, we identified several risk behaviors that may promote VVC and concluded that vaginal microbiologic analyses are urgently required in clinical practice in order to improve the prevention and treatment of this disease.